Heat transfer in a 3D cubic shell heat exchanger with rotating tubes and turbulent flow - Athraa Hameed Turki; Ali Khaleel Kareem; Ali M. Mohsen (Case Studies in Thermal Engineering)
This study investigated the thermal performance enhancement in a cubic shell heat exchanger (CSHE) equipped with rotating tubes and utilizing nanofluids under turbulent flow conditions. Water based nanofluids using Al₂O₃, SiO₂, ZnO, and CuO nanoparticles (diameters from 20 nm to 80 nm) were utilized under turbulent flow with concentrations ranging from 0 % to 2 %. The numerical simulations were carried out using the Reynolds-averaged Navier-Stokes (RANS) solver and the realizable k-ε turbulence model. It is shown a highest increase in Nusselt number of 15 % was achieved when using a 20 nm SiO₂ nanoparticles suspended in water compared to pure water. Further improvement in Nusselt number by up to 10 % was observed by increasing the nanoparticles volume fraction to 2 %. For Reynold’s numbers between 15000 and 30000, a 20 % improvement in the heat transfer was obtained due to increased turbulence. Surprisingly, the rotating inner tube introduced minimal effect compared to stationary configuration, with stationary tube slightly outperforming the rotating ones in most cases. The data suggests that significant enhancement in heat exchanger performance can be achieved by optimizing nanofluids properties and Reynold’s numbers, while tube rotations provided no additional benefits to the efficiency of the facility.